A case study of teacher modification strategies in an ESL classroom context - Rataza, Themba Theophilus (Rhodes University, Faculty of Education, Department of Education, 2006)
The purpose of this study is to explore and discuss the use of teacher modification strategies by a high school teacher in the Eastern Cape province of South Africa in an English second language classroom. This teacher does not share the mother tongue of the learners. Unlike other teachers who resort to code switching when teaching L2 learners, this particular educator does not have that liberty. Code switching has been found to be a useful strategy for teaching and learning (Adendorff 1996, Marawu 1996). Code switching will henceforth be abbreviated as CS in the rest of the text. Often teachers use CS to help students understand as an avoidance strategy to teach in English. They have no other way of getting through to students because they haven't been shown the benefits of teacher modification strategies employed by the teacher I have observed in this study. The study therefore seeks to establish or investigate and describe the modification strategies the teacher uses to make his lessons comprehensible to his learners and to accommodate the needs of his L2 learners in view of the fact that he does not share the language of his learners. The motivation behind this study stems from the difficulties experienced by L2/ESL learners learning through the medium of English. These problems are described by researchers such as Macdonald (1990), Eiseman (1992), NEPI report (1992). These difficulties relate to the lack of vocabulary, low proficiency levels and comprehension skills. In view of the above, this case study research was conducted on one teacher to find out or investigate how he modifies his teaching strategies. It has been revealed in the literature studied / reviewed that teachers employ a variety of teaching strategies to adapt to the needs of their L2 learners. (Long (1983), Wong-Filhnore (1985), Chaudron (1988), Huizenga et al (1990)). The teacher in this study has also been found to employ the main strategies to modify his teaching practice. It is clear from the interviews with both the teacher and his students, that this particular teacher makes full use of a range of language and methodological strategies to help his students understand his lessons. It is hoped that the findings of this research may illuminate some valuable insights in the necessity and usefulness of teacher modification strategies for all teacher trainers so that our teaching institutions can provide a variety of methods for teacher trainees to help L2 students develop their English language skills.
Keywords: English language -- Study and teaching (Foreign speakers) -- South Africa -- Eastern Cape; English language -- Study and teaching (Secondary) -- South Africa -- Eastern Cape; Code switching (Linguistics) -- South Africa Language and education -- South Africa